EDUGAMIFIKASI SEBAGAI STRATEGI INOVATIF UNTUK MENINGKATKAN KETERAMPILAN MEMBACA - Rini Kristiantari; Ni Kadek Annelika Candrakanti; Ni Luh Gede Puspa Ayu Sarif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading skills are a fundamental component of Indonesian language learning at the elementary school level; however, various challenges are still encountered in practice. This study aims to analyze the application of edugamification as an innovative strategy to improve students’ reading skills. This research employs a descriptive qualitative approach through a literature review supported by preliminary data obtained from SD CIS Bali, including learning conditions, teaching methods, and students’ difficulties in comprehending reading texts. The findings indicate that students’ reading interest is at a moderate level, with uneven participation between active and passive learners. The learning process is still dominated by lecture-based methods and assignments, which limit students’ active engagement. In addition, students experience difficulties in identifying main ideas and understanding implicit meanings in texts. Based on these findings, edugamification has the potential to be an effective instructional strategy to enhance student engagement, increase reading motivation, and support deeper comprehension through a more interactive and enjoyable learning environment.